Scale, Patriotism and Fun: Crossing the Last Frontier of Fantasy - Karal Ann Marling (Oz, 1986)
According to the rhetoric of a debate that erupted in Germany in 1933 under the leadership of Hermann Broch and was brought to a raging boil in America by Clement Greenberg in 1939, the California Sphinx is a prime example of "kitsch."